Social Images of Science and of Scientists, and the Imperative of Science Education for All - Aduriz Bravo, Agustin (2020)
In this chapter we examine the classic and renewed reasons that can be argued in order to support the need to teach science in compulsory education in the twenty-first century. We also discuss the currently proclaimed educational aims that configure the idea of a “quality science education for all”, traversed by equity and social justice. Science education founded on democratic values crucially needs: 1. explicitly addressing the dominant social imaginary around science and scientists in a critical way, and 2. designing and implementing pedagogies that are founded on, and present students with, a conception of the nature of science that is more aligned with recent philosophical proposals, leaving behind the “dogmatic” image of science. There is literature available on the transmission and strengthening of this dogmatic image through formal science education. Studies suggest that such view on the nature of science, still circulating at school, constitutes a relevant “didactical obstacle” for scientific literacy, and that this might be particularly relevant in the case of students coming from vulnerable backgrounds. Such findings constitute the moving force of this chapter and motivate reflections around the challenge of constructing a more adequate nature of science for a more socially just science education.